FACING BACK TO MOVE FORWARD: EVALUATING THE CONTRIBUTION OF THE INTERNATIONAL CRIMINAL TRIBUNAL OF RWANDA ON THE EVOLUTION OF INTERNATIONAL CRIMINAL LAW (The Pretoria Student Law Review, 2021)
The 1994 Rwanda genocide is one of the worst human catastrophes to have befallen mankind since World War II. The genocide left over 800 000 people dead, 1.7 million displaced, 400 000 widowed, and 130 000 arrested on suspicion of committing acts of genocide. The consequences of this genocide are still felt today. Despite the fact that the causes of this genocide were apparent, no commendable steps were taken by the international community, in particular the United Nations, to avert it. Having established that ‘genocide and other systematic, widespread and flagrant violations of international humanitarian law committed in Rwanda constituted a threat to international peace and security’ the UN adopted Resolution 955 which established the International Criminal Tribunal for Rwanda (ICTR). The ICTR was largely inspired by the International Criminal Tribunal for the former Yugoslavia (ICTY), a similar institution established for bringing those responsible for similar atrocities committed in the former Yugoslavia to justice. The ICTR has been largely criticised for taking too long when trying to dispose of the cases before it. At an international level, it is said that many funds are being spent on the ICTR without showing any results. These criticisms do not take the logistical, political and social challenges faced by the ICTR into account. At the time of its establishment, the ICTR faced mainly infrastructural challenges, thus it took almost three years for the ICTR to decide its first case. Most of its time was spent on putting an ICTR facility with three chambers in place. The wide-ranging criticisms tend to overshadow the achievements of the ICTR, which are highlighted in this paper.
Keywords: Rwanda genocide; United Nations; Resolution 955; International Criminal Tribunal for Rwanda; ICTR